Strategies to Develop Sawahlunto Old City in West Sumatera as Tourism Destination - Salam, Febby; Ingkadijaya, Rahmat; Hermantoro, Hengky (Jurnal Penelitian Pariwisata, 2018)
Tourism development in an area is able to give an impact on various dimensions of local people life. One of the impacts of tourism development is on the economic dimension. It happened to Sawahlunto, a city in West Sumatera famous for its coal mines, which slowly developed into a tourist city. The purpose of this study was to find out the Strength & Weakness, Opportunity & Threat and to formulate the development strategy of Kota Tua as a tourism destination in Sawahlunto, West Sumatra. The research method is descriptive method using SWOT analysis. The results showed that the development strategy of the Old City area of Sawahlunto used a lot of SWOT analysis, namely by increasing and optimizing natural resources through good processing, improving road access, and improving the tourism sector of Old City Sawahlunto. Another strategy is improving human resources through counseling and training, socialization of science and technology. The tourism potential of Sawahlunto old town on the 4A tourism component (Attraction, Accessibility, Amenities and Ancillary) shows that this area has the potential of historical tourist attraction. The historical heritage of World War II in Sawahlunto is the main tourism potential that is stored. With historical tourism potential, foreign tourists are the target of tourists who are expected to visit Sawahlunto. In order for a historical tourism potential strategy to be implemented, it is necessary to meet the minimum criteria of the tourism component. To meet the service standards of all 4A tourism components, it is necessary to improve the management of 4A tourism components including Attraction, Accessibility, Ancillary, and Amenity.